Uncertainty and Banks’ Security Holdings - Dang, Van Dan; Nguyen, Hoang Chung (The Indonesian Capital Market Review, 2022)
The paper enriches the existing literature on financial intermediaries’ operations in the face of uncertainty by empirically examining the impact of banking uncertainty on banks’ security holdings. Using bank-level data in Vietnam during 2007–2019 to compute a micro uncertainty proxy based on the dispersion of bank shocks, we document that banking uncertainty tends to enhance total security holdings at banks. Decomposing aggregate securities into disaggregate components, we find that safer investments (including government bonds and financial institution bonds) dominate the overall impact of banking uncertainty on security holdings, which completely offset a drop in the volume of riskier investments (including corporate bonds and stocks) in times of higher uncertainty. Furthermore, our analysis reveals that the impact of banking uncertainty on all security holdings is stronger at riskier banks, thereby implying that bank behavior is likely attributable to the precautionary motive.